EZH2 contributes to the response to PARP inhibitors through its PARP-mediated poly-ADP ribosylation in breast cancer - Yamaguchi, Hirohito (Oncogene, 2017)
Inhibitors against poly (ADP-ribose) polymerase (PARP) are promising targeted agents currently used to treat BRCA-mutant ovarian cancer and are in clinical trials for other cancer types, including BRCA-mutant breast cancer. To enhance the clinical response to PARP inhibitors (PARPi), understanding the mechanisms underlying PARP inhibitor sensitivity is urgently needed. Here, we show enhancer of zeste homolog 2 (EZH2), an enzyme which catalyzes H3 lysine trimethylation and associates with oncogenic function, contributes to PARPi sensitivity in breast cancer cells. Mechanistically, upon oxidative stress or alkylating DNA damage, PARP1 interacts with and attaches poly ADP-ribose (PAR) chains to EZH2. PARylation of EZH2 by PARP1 then induces PRC2 complex dissociation and EZH2 downregulation, which in turn reduces EZH2-mediated H3 tri-methylation. In contrast, inhibition of PARP by PARPi attenuates alkylating DNA damage-induced EZH2 downregulation, thereby promoting EZH2-mediated gene silencing and cancer stem cell property compared to PARPi-untreated cells. Moreover, the addition of an EZH2 inhibitor sensitizes the BRCA-mutant breast cells to PARPi. Thus, these results may provide a rationale for combining PARP and EZH2 inhibition as a therapeutic strategy for BRCA-mutated breast and ovarian cancers.